Examining gun regulations, warning behaviors, and policies to prevent mass shootings - Kerr, Selina E. M. (Advances in human services and public health (AHSPH) book series, 2021)
"This book investigates and analyzes the debates around and responses to mass shootings, covering the prevention, preparation, response and recovery of mass shootings as well as gun proposals introduced and raised following each incident"--